Determination of Strength and Deformation Parameters of Remolded Clays by Falling Cone and Veyn Tests - Gulen, Murat; Kilic, Havvanur (TURKISH CHAMBER CIVIL ENGINEERS, 2020)
In practice, the shear vane test is used to predict the undrained shear strength of remolded and undisturbed clay soils. The undrained shear strength could also be estimated for remolded soils by the fall cone test. However, the determination of undrained shear strength by this test requires a very significant factor which is referred to as fall cone factor. The drained internal friction angle could be obtained by using the fall cone factor, calibrated in accordance with experimental results and the values of undrained shear strength calculated for different water contents and void ratios at critical state. In this study, compressibility and strength parameters were determined practically on remolded samples of cohesive soils with different index proporties by using the methods proposed in the literature. In addition, the applicability of the method used was evaluated for the same soil by comparing the compressibility and strength parameters obtained from oedometer and triaxial compression tests.
Keywords: Remolded clay; critical state parameters; fall cone test; Engineering